F508del disturbs the dynamics of the nucleotide binding domains of CFTR before and after ATP hydrolysis. Issue 1 (17th July 2019) - Abreu, Bárbara; Lopes, Emanuel F.; Oliveira, A. S. F.; Soares, Cláudio M.
Abstract: The cystic fibrosis transmembrane conductance regulator (CFTR) channel is an ion channel responsible for chloride transport in epithelia and it belongs to the class of ABC transporters. The deletion of phenylalanine 508 (F508del) in CFTR is the most common mutation responsible for cystic fibrosis. Little is known about the effect of the mutation in the isolated nucleotide binding domains (NBDs), on dimer dynamics, ATP hydrolysis and even on nucleotide binding. Using molecular dynamics simulations of the human CFTR NBD dimer, we showed that F508del increases, in the prehydrolysis state, the inter‐motif distance in both ATP binding sites (ABP) when ATP is bound. Additionally, a decrease in the number of catalytically competent conformations was observed in the presence of F508del. We used the subtraction technique to study the first 300 ps after ATP hydrolysis in the catalytic competent site and found that the F508del dimer evidences lower conformational changes than the wild type. Using longer simulation times, the magnitude of the conformational changes in both forms increases. Nonetheless, the F508del dimer shows lower C‐α RMS values in comparison to the wild‐type, on the F508del loop, on the residues surrounding the catalytic site and the portion of NBD2 adjacent to ABP1. These results provide evidence that F508del interferes with the NBD dynamics before and after ATP hydrolysis. These findings shed a new light on the effect of F508del on NBD dynamics and reveal a novel mechanism for the influence of F508del on CFTR.